Laryngeal mobility and dysphagia - Bretan, Onivaldo [UNESP]; Henry, Maria Aparecida A. (My University, 1997)
The authors studied the utility of the physical test of laryngeal movement in swallowing disorders of the oropharyngeal region. Measurement and palpation of the larynx during deglutition were performed in the neck of 14 dysphagic patients and in two normal control groups. The normal groups were used to establish the pattern of the movement and the normal values of laryngeal elevation. Control elevation ranged from 1.80 to 2.50 cm. In eight patients laryngeal motion was defective and presented values ranging from zero to 1.50 cm. Palpation during laryngeal movement also revealed unexpected anomalous displacement such as lateral shifting and lowering of the larynx. In six patients with defective laryngeal motion, pharyngeal and upper esophageal sphincter function were also impaired. Direct measurement and palpation of laryngeal mobility during deglutition is a noninvasive method that can be used to evaluate dysphagia and the risk for aspiration. Also, it allows physical assessment of the evolution of the disorder.
Keywords: Deglution disorders; Larynx; Physiology; adult; aged; dysphagia; female; human; larynx; male; middle aged; palpation; physiology; Adult; Aged; Aged, 80 and over; Deglutition Disorders; Female; Humans; Male; Middle Aged; Palpation